Key ideas in linguistics and the philosophy of language [ - Chapman, Siobhan , 1968-; Routledge, Christopher , 1968- (Edinburgh University Press, 2009)
This book offers introductory entries on 80 ideas that have shaped the study of language up to the present day. Entries are written by experts in the fields of linguistics and the philosophy of language to reflect the full range of approaches and modes of thought. Each entry includes a brief description of the idea, an account of its development, and its impact on the field of language study. The book is written in an accessible style with clear descriptions of technical terms, guides to further reading, and extensive cross-referencing between entries. A useful additional feature of this book